Rancang Bangun Mesin Press Karet Dari Lateks Menjadi Sheet Skala Home Industry - Andi Widiyanto Prasetyo; Antonius FA Silaen (MAJALAH TEKNIK SIMES, 2022)
Abstract Rubber press machine is a tool used to press rubberfrom lumps into sheets or sheets that have been determined in thickness. This machine works with three pairs of rolls and after calculating the planning of the rubber press machine, the roll size is obtained: length 500 mm, Roll Diameter 76.2 mm, with 3 inch pipe iron material. Rubber press machine power 0.09628 kW, speed 0.204653 m/second. Motor power 0.17035 kW. Shaft, Diameter of shaft 20 mm, Material of shaft carbon steel, Moment of torsion of shaft 2736,7635 kg/mm2, Shaft shear stress 361,74468 kg/mm2. Frame, Frame length 150 cm, Frame height 110 cm, frame width 60 cm. Pegs, 7 mm width of the key, 30 mm of key length, 7 mm of key thickness, 4 mm of keyway depth on the shaft, Shear stress on the key, 1,303 kg/mm2, Allowable shear stress on the post 3,055 kg/mm2. Pully, pulley ratio A : 4, pulley belt speed 3.88 m/s, pully diameter 203.2 mm, pully rotation 365 rpm, shaft axis distance 320 mm. Comparison of pully B: 2.6667, speed of belt pully 1.455 m/sec, length of belt 1118,048 mm, diameter of pully 203.2 mm, rotation of pully 136.87 rpm, axle distance of 240 mm. Comparison of pully C: 2.6669, speed of pully belt 0.545 m/sec, belt length 1118,048 mm, pully diameter 203.2 mm, pully rotation 51.32 rpm, shaft axis distance 240 mm. Comparison of pulleys D and E: 1, pulley belt speed 0,545 m/sec, belt length 1318,048 mm, pully diameter 203.2 mm, pully rotation 51.32 rpm, shaft axis distance 340 mm. Bearing, Bearing number 6004, Inner diameter 20 mm, Outside diameter 42 mm, Bearing width 12 mm, Dynamic nominal capacity 735 kg, Static nominal capacity 465 kg, Axial load 51.15 kg, Radial load 170.5 kg, Dynamic equivalent load 169.6475 kg, Static equivalent radial load 196.675 kg.